2013
DOI: 10.1007/978-3-642-36620-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time 2D/3D Deformable Registration Using Metric Learning

Abstract: Abstract. We present a novel 2D/3D deformable registration method, called Registration Efficiency and Accuracy through Learning Metric on Shape (REALMS ), that can support real-time Image-Guided Radiation Therapy (IGRT ). The method consists of two stages: planning-time learning and registration. In the planning-time learning, it firstly models the patient's 3D deformation space from the patient's time-varying 3D planning images using a low-dimensional parametrization. Secondly, it samples deformation paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The findings by Chou et al [2] indicate that REALMS performs reasonably well in lung. However, there are additional challenges posed by registration in abdomen.…”
Section: Localized Realms In the Abdomenmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings by Chou et al [2] indicate that REALMS performs reasonably well in lung. However, there are additional challenges posed by registration in abdomen.…”
Section: Localized Realms In the Abdomenmentioning
confidence: 99%
“…As described in [2], REALMS first models the deformation with a shape space, in which each deformation is formed by a linear combination of basis deformations calculated through PCA analysis. For deformations due to respiration, we use a set of RCCT images { J τ |τ = 1, 2, …, 10} of the patient at planning time that records a cyclically varying target area.…”
Section: Realms Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In our review we found that unsupervised representation learning techniques are a widely adopted technique to reduce the dimensionality of the parameter space while introducing implicit regularization by confining possible solutions to the principal modes of variation across population- or patient-level observations. We identified 12 studies that propose such techniques or use them as part of the registration pipeline ( Brost et al, 2012 ; Lin and Winey, 2012 ; Chou and Pizer, 2013 , 2014 ; Chou et al, 2013 ; Zhao et al, 2014 ; Baka et al, 2015 ; Pei et al, 2017 ; Chen et al, 2018 ; Zhang et al, 2018 ; Foote et al, 2019 ; Li et al, 2020 ; Zhang et al, 2020 ).…”
Section: Systematic Reviewmentioning
confidence: 99%